Differential Utilization of Ras Signaling Pathways by Macrophage Colony-Stimulating Factor (CSF) and Granulocyte-Macrophage CSF Receptors during Macrophage Differentiation - Guidez, Fabien (American Society for Microbiology, 1998)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) and macrophage colony-stimulating factor (M-CSF) independently stimulate the proliferation and differentiation of macrophages from bone marrow progenitor cells. Although the GM-CSF and M-CSF receptors are unrelated, both couple to Ras-dependent signal transduction pathways, suggesting that these pathways might account for common actions of GM-CSF and M-CSF on the expression of macrophage-specific genes. To test this hypothesis, we have investigated the mechanisms by which GM-CSF and M-CSF regulate the expression of the macrophage scavenger receptor A (SR-A) gene. We demonstrate that induction of the SR-A gene by M-CSF is dependent on AP-1 and cooperating Ets domain transcription factors that bind to sites in an M-CSF-dependent enhancer located 4.1 to 4.5 kb upstream of the transcriptional start site. In contrast, regulation by GM-CSF requires a separate enhancer located 4.5 to 4.8 kb upstream of the transcriptional start site that confers both immediate-early and sustained transcriptional responses. Results of a combination of DNA binding experiments and functional assays suggest that immediate transcriptional responses are mediated by DNA binding proteins that are constitutively bound to the GM-CSF enhancer and are activated by Ras. At 12 to 24 h after GM-CSF treatment, the GM-CSF enhancer becomes further occupied by additional DNA binding proteins that may contribute to sustained transcriptional responses. In concert, these studies indicate that GM-CSF and M-CSF differentially utilize Ras-dependent signal transduction pathways to regulate scavenger receptor gene expression, consistent with the distinct functional properties of M-CSF- and GM-CSF-derived macrophages.